2022
DOI: 10.1093/braincomms/fcac221
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in social interaction and hippocampal long-term potentiation at perforant pathway-dentate gyrus synapses in a prenatal valproic acid-induced rat model of autism

Abstract: It is well established that prenatal valproic acid exposure in rats leads to autism-like behaviors and social deficits. Long-term potentiation changes in the brain have been proposed as a potential mechanism in the development of autistic behaviour. However, there are controversies regarding the effect of in utero valproic acid exposure on long-term potentiation. This study examined the social interaction, and long-term potentiation induction in perforant pathway-dentate gyrus synapses in male offspring of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Notably, the HTX-offspring, regardless of sex, showed extended interaction with the first social stimulus compared to the new one ( Figure 5 , Supplementary Tables 1-1.4a-l ). These trends were concordant with previous observations in different ASD-like models, including MIA and VPA offspring, where males tend to manifest more pronounced deficits in social interaction abilities ( 82 , 83 ). In the context of the three-chamber test, these results are indicators of impaired social skills, which are widely recognized to correlate with recurring ASD-like behaviors in both humans and mice ( 84 86 ).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the HTX-offspring, regardless of sex, showed extended interaction with the first social stimulus compared to the new one ( Figure 5 , Supplementary Tables 1-1.4a-l ). These trends were concordant with previous observations in different ASD-like models, including MIA and VPA offspring, where males tend to manifest more pronounced deficits in social interaction abilities ( 82 , 83 ). In the context of the three-chamber test, these results are indicators of impaired social skills, which are widely recognized to correlate with recurring ASD-like behaviors in both humans and mice ( 84 86 ).…”
Section: Discussionsupporting
confidence: 92%
“…we observed no gestational CIH-associated changes in proteins associated with glutamatergic, dopaminergic, and serotonergic functions, regardless of sex or age of the offspring. We also examined markers for cellular activity (EGR-1) and neurogenesis (doublecortin) within the dentate gyrus region of the dorsal hippocampus, as cellular activity and neurogenesis within the dentate gyrus is important in mediating spatial memory [120,121] and social function [67-70], as well as being associated with ASD [122,123]. We found no effects of late gestational CIH on EGR-1 or doublecortin protein expression in the dentate gyrus, regardless of sex or age.…”
Section: Discussionmentioning
confidence: 94%
“…We found no effects of late gestational CIH on EGR-1 or doublecortin protein expression in the dentate gyrus, regardless of sex or age. Future studies need to be conducted to examine the electrophysiological properties (long-term potentiation and long-term depression) of dorsal hippocampal neurons and neurogenesis (bromodeoxyuridine, BrdU), as dysfunction in these cellular properties have been linked with ASD [122,123].…”
Section: Discussionmentioning
confidence: 99%
“…Even fewer studies have looked at possible differences in gene expression or brain structure/function between male and female rodents with ASD-like behavior. Some researchers have used only males, to eliminate possible sex differences [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ] in behaviors, such as anxiety-related behaviors and repetitive behaviors [ 139 , 140 ]. Kataoka et al [ 140 ] found that prenatal VPA in mice induced transient histone hyper-acetylation in the brains of offspring of male and female mice.…”
Section: Sex-related Differences In Non-genetic Animal Models Of Asd:...mentioning
confidence: 99%